Personal meaning: van narratieve analyse tot geestelijke zorg - Ellen Oosting; Willem Marie Speelman (Religie & Samenleving)
The religious origins of medical care tell us that care is always also a manner of coping with the uncontrollable sides of life. Present day medical care, however, finds it difficult to deal with this manner of coping, because it is a very personal and individualized matter. On the other hand, the personal manner of coping – religiously, spiritually or other – is considered an important aspect of care practice. The (spiritual) councelor may have a special role in this process and develop special skills in order to assist it. This article investigates coping with the uncontrollable sides of life as a personal involvement in which meaning is generated. By a narrative analysis of the stories of three different persons involved in this process – the patient, her daughter and the physical therapist – we can follow how they are generating meaning together. Relying on powers of motivation, collecting or hoping for competences, the patient tries to realize a valuable situation, transforming an uncontrollable into a meaningful life event. The daughter and physical therapist, each one following their own program are helping the patient. The narrative approach of personal meaning may help the councelor to follow the manner in which a person copes with his or her situation, and to tune the programs of different persons involved in this situation to one another.